Strengthening Educational Literacy Through Community Learning Assistance at Sanggar Bimbingan Sungai Mulia 5 - Masruatus Saadah (Journal of Conflict and Social Class (JCSC), 2025)
Educational literacy plays an important role in supporting children’s academic development, communication competence, and social participation in contemporary society. Children from migrant and marginalized communities often experience educational challenges related to literacy development, learning motivation, and limited access to educational resources. This community service program aims to strengthen educational literacy through community learning assistance at Sanggar Bimbingan Sungai Mulia 5. The program employed a qualitative participatory approach involving school-age children from Indonesian migrant communities through interactive learning activities, literacy mentoring, collaborative educational exercises, and digital literacy integration. Educational activities included guided reading sessions, storytelling, vocabulary exercises, group discussions, educational games, and collaborative learning practices designed to improve literacy competence and student engagement. The results demonstrated significant improvement in students’ reading comprehension, communication confidence, classroom participation, learning motivation, and social interaction. In addition, participatory learning methods and supportive mentoring contributed positively to students’ emotional confidence and collaborative learning abilities. The integration of digital educational media also strengthened students’ familiarity with educational technology and interactive learning resources. Despite challenges related to differences in literacy competence, learning concentration, and limited educational resources, adaptive teaching methods and continuous mentoring supported the successful implementation of the program. Overall, the community learning assistance activities provided valuable opportunities for strengthening educational literacy, educational participation, and student empowerment within migrant learning communities. The implementation of this program also demonstrates that community-based literacy education can contribute positively to sustainable educational development and social empowerment among vulnerable educational groups.